Light Availability and Salt Stress on Hazel Sterculia Seedlings - Lima,Breno Leonan de Carvalho (2018)
ABSTRACT The objective of this study was to evaluate the effect of light availability and salt stress on the growth and quality of hazel sterculia seedlings. The experiment was conducted with two light conditions – full sun (L1), and 50% shading (L2) – and five salinity levels in the irrigation water – 1.0 (S1), 2.2 (S2), 3.2 (S3), 4.2 (S4), and 5.1 (S5) dS m-1. The environment with 50% shading was the most suitable to produce hazel sterculia seedlings, even under high salinity (5.1 dS m-1). Increasing salinity negatively affects the growth and quality of hazel sterculia seedlings. Therefore, controlling sunlight availability and irrigation water saline conditions increases rooting potential and seedling survival in the field.